2021
DOI: 10.1002/adfm.202105807
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight‐Sensitive Plasmonic Nanostructured Composites as Photocatalytic Coating with Antibacterial Properties

Abstract: Infections caused by microorganisms are a global public health problem that continually demands new antimicrobial strategies. The generation of reactive oxygen species (ROS) by photocatalytic materials is an attractive approach to combat microbes. Along these lines, titanium dioxide (TiO 2 ) constitutes an outstanding light-driven ROS generator. However, the wide bandgap of this semiconductor limits its use to the ultraviolet range of the spectral region. Herein, nanostructured materials composed of TiO 2 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…It was found that these AgNP colloids have excellent photocatalytic activity and are capable of producing reactive oxygen species (ROS) under visible light irradiation. In general, ROS have broad-spectrum biocidal effects and also play an important role in the orchestration of the wound healing response, since they act as secondary messengers to immunocytes and nonlymphoid cells, regulating the angiogenesis at the wound site. …”
Section: Introductionmentioning
confidence: 99%
“…It was found that these AgNP colloids have excellent photocatalytic activity and are capable of producing reactive oxygen species (ROS) under visible light irradiation. In general, ROS have broad-spectrum biocidal effects and also play an important role in the orchestration of the wound healing response, since they act as secondary messengers to immunocytes and nonlymphoid cells, regulating the angiogenesis at the wound site. …”
Section: Introductionmentioning
confidence: 99%
“…Although studies of sunlighttriggered nanomaterials are limited, with the development of visible photocatalysts, sunlight-enabled antibacterial nanomaterials will attract increasing attention. [60,61]…”
Section:  Photo-mediated Bacterial Killingmentioning
confidence: 99%
“…Marín-Caba et al presented a TiO 2 /AuNRs composite for bacteria photoinactivation, aiming to expand the photocatalysis action to the visible and near-infrared ranges. Upon sunlight irradiation, the composites exhibited strong biofilms inactivation and antimicrobial activity (Figure A) . Meanwhile, Wu et al synthesized a Schottky heterojunction photocatalyst (Ag 2 S/Ti 3 C 2 ) to treat bacteria infections after exposure of 808 nm light, and the efficacy was up to 99.99% within 20 min (Figure B) …”
Section: Design Strategies For Improving Photocatalytic Performancementioning
confidence: 99%